Differential endocytosis and signaling dynamics of insulin receptor variants IR-A and IR-B - Giudice, Jimena (2011)
Insulin signaling comprises a complex cascade of events, playing a key role in the regulation of glucose metabolism and cellular growth. Impaired response to insulin is the hallmark of diabetes, whereas upregulated insulin activity occurs in many cancers. Two splice variants of the insulin receptor (IR) exist in mammals: IR-A, lacking exon 11, and full-length IR-B. Although considerable biochemical data exist on insulin binding and downstream signaling, little is known about the dynamics of the IR itself. We created functional IR transgenes fused with visible fluorescent proteins for use in combination with biotinamido-caproyl insulin and streptavidin quantum dots. Using confocal and structured illumination microscopy, we visualized the endocytosis of both isoforms in living and fixed cells and demonstrated a higher rate of endocytosis of IR-A than IR-B. These differences correlated with higher and sustained activation of IR-A in response to insulin and with distinctive ERK1/2 activation profiles and gene transcription regulation. In addition, cells expressing IR-B showed higher AKT phosphorylation after insulin stimulation than cells expressing IR-A. Taken together, these results suggest that IR signaling is dependent on localization; internalized IRs regulate mitogenic activity, whereas metabolic balance signaling occurs at the cell membrane.